A distance-learning Course on Indoor Environmental Comfort in Buildings - Silva, Manuel Gameiro da (2017)
A project for the creation and implementation of a distancelearning course on Indoor Environmental Comfort in Buildings (IECB) is presented. This course resulted from a request by Ordem dos Engenheiros (Portuguese engineering professional body) to the University of Coimbra. It was based on the Indoor Environmental Quality (IEQ) course of the Master in Energy for Sustainability and PhD in Sustainable Energy Systems of the University of Coimbra, coordinated by the first author. Jointly with the support of the Distance Education Service of the University of Coimbra, using as a starting point the existing contents of a formal discipline, the teaching methodologies and a set of activities were developed to implement a distance-learning course with a strong e-learning component by the students. Diversified strategies, using the existing platform running on Moodle, such as webinars, virtual laboratories, remote access labs, discussion forums and synchronous sessions, were tested to ensure a dynamic and interested engagement of the students along the course.